Regulation of activin A synthesis in microglial cells: pathophysiological implications for bacterial meningitis - Wilms, Henrik; Schwark, Thorsten; Brandenburg, Lars-Ove; Sievers, Jobst; Dengler, Reinhard; Deuschl, Günther; Lucius, Ralph (Journal of neuroscience research, 2010)
Previous studies have shown that activin A, a neuroprotective cytokine and dimeric polypeptide composed of two βA subunits, is elevated in the cerebrospinal fluid of patients suffering from bacterial meningitis. In this study, to elucidate further the functional significance and pathophysiological implications of these findings, we demonstrated that microglial cells are not only the source but also the target cells of activin A in the central nervous system: immunohistochemistry and RT-PCR revealed expression of activin subunit βA mRNA as well as activin receptor type I and type II mRNA in rat microglia in vitro. Further studies showed that activin enhances microglial proliferation and decreases the γ-interferon-induced synthesis of nitric oxide, one of several microglial mediators involved in the inflammatory response in microglia activation. Furthermore, quantitative RT-PCR, Western blotting, and ELISA showed an inhibitory effect of activin on inducible nitric oxide synthase, tumor necrosis factor-α, interleukin-6, and interleukin-1β gene and protein levels after lipopolysaccharide treatment. We suggest that the increased synthesis of activin A is directly involved, via influence on microglia cell functions, in the modulation of the inflammatory response in bacterial meningitis. © 2009 Wiley-Liss, Inc.